Peningkatan Motivasi Belajar Siswa Melalui Papan Pintar - Fadhli, Khotim; Kusen, M. Sahrul; Hasanah, Naslatul; Arianti, Jihan Kamilah; Putra, Ino Angga Putra; Miruki, S. Sukowati Wanafaktu; Devinta, Olivia Ekka; Huda, Moch. Faizul (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2025)
Primary education plays a crucial role in building the learning foundation for students, especially at the elementary school level. One of the biggest challenges is maintaining students' learning motivation, which often decreases due to monotonous teaching methods. To address this, innovative learning media such as Smart Boards provide an effective solution. These media can create an interactive and enjoyable learning experience, enhancing students' motivation and engagement. The community service project by Universitas KH. A. Wahab Hasbullah (Unwaha) at SDN Ketapangkuning aims to introduce simple Smart Boards, address learning motivation challenges, and provide flood disaster mitigation education relevant to the local environment. The activities involve direct mentoring for teachers and students from grades 4 to 6, along with flood prevention awareness campaigns. As a result, students showed increased learning motivation, with 85% feeling more enthusiastic, and 90% understanding the importance of environmental preservation. Evaluations through questionnaires and discussions indicated positive impacts in both learning and environmental awareness. Despite facing challenges such as limited resources and differences in student understanding, the project significantly contributes to improving education quality and disaster preparedness at SDN Ketapangkuning.